2016
DOI: 10.1113/ep085632
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia attenuates cardiopulmonary reflex control of sympathetic nerve activity during mild dynamic leg exercise

Abstract: New Findings r What is the central question of this study?The cardiopulmonary baroreflex inhibits adjustment of sympathetic vasomotor outflow during mild-intensity dynamic exercise. However, it is unclear how suppression of sympathetic vasomotor outflow by the cardiopulmonary baroreflex is modulated by a powerful sympatho-excitatory drive from the exercise pressor reflex, central command and/or the arterial chemoreflex. r What is the main finding and its importance?Hypoxia-induced heightened sympathetic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Others investigating resting MSNA have found considerable between subject variability . Similarly, the current study and others utilizing dynamic exercise found variability in MSNA at a given external work rate (Watts) or Wb. For example, in Figure Panel A, at any intensity and for a given relative Wb, the MSNA BF varies ~15% of maximal levels.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Others investigating resting MSNA have found considerable between subject variability . Similarly, the current study and others utilizing dynamic exercise found variability in MSNA at a given external work rate (Watts) or Wb. For example, in Figure Panel A, at any intensity and for a given relative Wb, the MSNA BF varies ~15% of maximal levels.…”
Section: Discussionsupporting
confidence: 74%
“…The recording of MSNA from the upper limb during leg cycling is technically difficult. Furthermore, most investigations have recording MSNA during low intensity exercise (<50% normalV˙normalO2 ). As such, a secondary purpose of our study was to provide a quantitative assessment of MSNA during heavy exercise.…”
Section: Introductionmentioning
confidence: 99%
“…We used 40% V̇O2 peak exercise intensity for several reasons, as in our previous study, because the rate of successful MSNA recordings is relatively high when the exercise intensity is light (Katayama et al., , , , ). Movements of the arm and the body become greater during leg cycling with inspiratory resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mean voltage neurogram was continuously digitized through an analog-to-digital converter with a sampling frequency of 200 Hz. The MSNA bursts were identified from the mean voltage neurogram using a customized computer program-assisted inspection (Katayama et al, 2015;Katayama, Ishida, Saito, Koike, & Ogoh, 2016), which accounted for the latency from the ECG R wave to the sympathetic burst (Fagius & Wallin, 1980). The MSNA was quantified as burst frequency (BF; in bursts per minute) and burst incidence (BI; in bursts per 100 heart beats).…”
Section: Muscle Sympathetic Nerve Activitymentioning
confidence: 99%
“…This is made possible by a cellular HIF system. Cellular hypoxia, or a lower than "normal" concentration of O 2 in cells, occurs commonly and could induce signiicant changes, immediate or delayed, on cellular processes, including cell growth and apoptosis, cell proliferation and survival, pH regulation and energy metabolism, cell migration, matrix and barrier function, angiogenesis, and vasomotor regulation [8][9][10][11][12][13]. These biological processes involve active responses by the body to secure an additional oxygen supply via circulation.…”
Section: Hypoxia In the Oral/periodontal Environmentmentioning
confidence: 99%